1989
DOI: 10.1007/bf02553486
|View full text |Cite
|
Sign up to set email alerts
|

Significance of lateral node dissection for advanced rectal carcinoma at or below the peritoneal reflection

Abstract: Two hundred thirty two patients with rectal cancer at or below the peritoneal reflection, who underwent extended systematic lymphadenectomy, especially lateral node dissection, were reviewed with respect to survival rate, degree of surgical technique, and mode of recurrence. On the basis of the extent of lateral node spread, two types of lateral node dissection were performed, consisting of preservation of internal iliac vessels (conventional) and en bloc excision of these vessels (extended). The overall disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0
5

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(148 citation statements)
references
References 10 publications
3
140
0
5
Order By: Relevance
“…Extended lateral dissection beyond the extent of TME has been widely accepted in Japan as the improvement in survival rates was reported [28,29] , but some argued that it had a limited advantage in prognosis and the functional problems were considerable [30,31] . Microscopic tumor nodule involvement of CRM after TME in our series suggested that a proportion of the patients had microscopic tumor spread in the extramesorectal regions in the pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…Extended lateral dissection beyond the extent of TME has been widely accepted in Japan as the improvement in survival rates was reported [28,29] , but some argued that it had a limited advantage in prognosis and the functional problems were considerable [30,31] . Microscopic tumor nodule involvement of CRM after TME in our series suggested that a proportion of the patients had microscopic tumor spread in the extramesorectal regions in the pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical importance of the lateral spread of lower rectal cancer was first demonstrated in the 1950s (23). Since then, LPLD was performed for middle or lower rectal cancer in Japan, because the incidence of lateral LN metastasis in patients with lower rectal cancer is high (13-18%) (7,24,25). This procedure is associated with a lower local recurrence rate than conventional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…were mixed with lymphocytes (1x10 7 ) obtained from healthy volunteers (that did not express CEA mRNA). Total RNA was extracted from each mixture and subjected to a quantitative RT-PCR assay.…”
Section: Rt-pcr Sensitivity In Detecting Cancer Cells Serial Dilutiomentioning
confidence: 99%
See 1 more Smart Citation
“…Na casuística anterior do Serviço, a recidiva locorregional ocorreu em 20% dos casos (13) . As taxas de recorrência local, no mundo, variam de 20 a 45% (10,16,(27)(28)(29) . Sabe-se que os melhores índices obtidos até hoje foram de 2,6% com a ressecção total do mesorreto (10,30) .…”
Section: Variávelunclassified